Floor Substrate Preferences of Chickens: A Meta-Analysis - Monckton, Valerie; Ellis, Jennifer L.; Harlander-Matauschek, Alexandra (Frontiers in veterinary science, 2020)
Environmental enrichment promotes sensory and motor stimulation for species-typical behaviors, which in turn enhance animal well-being. For farmed Galliformes, housing systems often limit enrichment to bedding and litter, that simultaneously act as material for dustbathing and foraging. Therefore, this meta-analysis sought to systematically review and synthesize the substrate preference test literature for Galliformes. Data based on the following four welfare-related behaviors were extracted for analysis: (1) dustbathing, (2) foraging, (3) pecking, and (4) time spent on a given substrate. Literature searches in CAB Direct, Web of Science, and Google Scholar yielded 239 articles, and hand searching yielded an additional five articles. Ten publications that used different chicken strains as test subjects, met the criteria to be included in the systematic review. The effects of bedding type, the number of days birds had access to tested substrates, enclosure area, and substrate area, on the examined behaviors were determined. We found that birds preferred dustbathing in sand and peat moss more than on any other substrates. The bedding type, size of the enclosure, and size of the substrate area affected the amount of time that birds spent on the tested substrates. When provided the choice between bedding materials, birds spent more time on sand or peat moss than on any other substrate or on no substrate. Notably, most studies did not report relevant physical or chemical characteristics of substrate that may influence birds' preferences, such as grain size, moisture content and the level of soiling. Focusing future studies on identifying substrate characteristics that influence preferences can lead to the discovery of new, practical, enriching beddings that can be easily implemented in housing systems for Galliformes.